2014
DOI: 10.1088/0964-1726/23/2/025032
|View full text |Cite
|
Sign up to set email alerts
|

A smart dynamic vibration absorber for suppressing the vibration of a string supported by flexible beams

Abstract: This study aims to effectively and robustly suppress the vibration of tension-stabilized structures (TSSs) using a smart dynamic vibration absorber (DVA). In recent years, a strong need has emerged for high-precision and high-functionality space structural systems for realizing advanced space missions. TSSs have attracted attention in this regard as large yet lightweight structural systems with high storage efficiency. A fundamental issue in the application of TSSs is vibration control of strings, of which TSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…After dropping the DVA from the equation of motion in the previous section, we obtain the following: (13) In this model, the two ends are hinged; therefore, the boundary conditions are…”
Section: Equation Of Motion For the Nonlinear Beam Without Dvamentioning
confidence: 99%
See 1 more Smart Citation
“…After dropping the DVA from the equation of motion in the previous section, we obtain the following: (13) In this model, the two ends are hinged; therefore, the boundary conditions are…”
Section: Equation Of Motion For the Nonlinear Beam Without Dvamentioning
confidence: 99%
“…They found that placing a DVA of appropriate mass could prevent internal resonance and suppress vibrations in the beam. Nambu et al 13 studied the smart self-sensing active DVA attached on a flexible beams supported string. A small cantilevered piezoelectric transducer was used to realize this active DVA.…”
Section: Introductionmentioning
confidence: 99%
“…DVAs with a controllable natural frequency range are widely developed to meet the requirements of the shift-frequency vibration absorption. The elastic elements of DVAs are often synthesized using smart materials, such as magnetorheological (MR) materials, electrorheological (ER) materials, and piezoelectric ceramics (Anh and Nguyen, 2016;Davis and Lesieutre, 2000;Nambu et al, 2014;Thompson, 1981). Magnetorheological elastomers (MREs) are one kind of MR materials based on nonmagnetic elastic matrices filled with micro-sized magnetizable particles (Jolly et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in some ''fast-speed moving'' or ''high precision need'' working conditions, much additional time should be spent to eliminate the vibration. [9][10][11] In the self-propelled howitzer (SPH), the flexible mechanical arms system is applied to the device which used to auto-load. The vibration caused by the impact of bullet and the recoil of howitzer would affect the whole circulation time in loading and decrease the firing rate of SPH.…”
Section: Introductionmentioning
confidence: 99%